2017
DOI: 10.1007/s00442-017-3925-1
|View full text |Cite
|
Sign up to set email alerts
|

A salty landscape of fear: responses of fish and zooplankton to freshwater salinization and predatory stress

Abstract: Predator-prey relationships are altered by anthropogenic contaminants. Road salt is a widespread contaminant among freshwater ecosystems, yet a relatively understudied subject in community ecology. Unknown is whether road salt salinization interacts with predatory stress to influence the growth, behavior, or reproduction of freshwater organisms. Using rainbow trout (Oncorhynchus mykiss) and zooplankton (Daphnia pulex), we exposed them to variable levels of road salt (NaCl) crossed with the presence or absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…One study found that predatory fish acted synergistically to increase the mortality of native clams (Sphaerium simile) at 1,000 mg Cl − /L, perhaps due to the costs of predator avoidance and osmotic stress . resting egg production in Daphnia pulex) can be inhibited by osmotic stress resulting from road salt concentrations ≥230 mg Cl − /L (Hintz & Relyea, 2017b). Although this effect triggered a trophic cascade leading to phytoplankton blooms, the authors found few effects in the absence of fish predation on zooplankton communities, perhaps due to rapid adaptation of zooplankton to the salt concentrations (Coldsnow, Mattes, Hintz, & Relyea, 2017;Hintz, Jones, & Relyea, 2019).…”
Section: Lake Communitiesmentioning
confidence: 97%
See 3 more Smart Citations
“…One study found that predatory fish acted synergistically to increase the mortality of native clams (Sphaerium simile) at 1,000 mg Cl − /L, perhaps due to the costs of predator avoidance and osmotic stress . resting egg production in Daphnia pulex) can be inhibited by osmotic stress resulting from road salt concentrations ≥230 mg Cl − /L (Hintz & Relyea, 2017b). Although this effect triggered a trophic cascade leading to phytoplankton blooms, the authors found few effects in the absence of fish predation on zooplankton communities, perhaps due to rapid adaptation of zooplankton to the salt concentrations (Coldsnow, Mattes, Hintz, & Relyea, 2017;Hintz, Jones, & Relyea, 2019).…”
Section: Lake Communitiesmentioning
confidence: 97%
“…They also generate valuable ecosystem services through alevins (Oncorhynchus mykiss) exposed to NaCl road salt for 25 days (well after they developed into free-swimming fry) experienced a 9% reduction in length and 27% reduction in mass at 3,000 mg Cl − /L for NaCl (Hintz & Relyea, 2017a). In a subsequent experiment, the same species was tested at a later life stage and NaCl road salt at 2,000 and 4,000 mg Cl − /L did not affect rainbow trout growth (Hintz & Relyea, 2017b). Compared with other freshwater species, fish appear to be relatively tolerant to salt, but a broader assessment of obligate freshwater fish species is needed because reductions in fish growth may influence recruitment and population growth (Milner et al, 2003).…”
Section: Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated the effects of freshwater salinity on species interactions (Céspedes, Sánchez, & Green, ; Hintz & Relyea, ; Liu & Steiner, ; Piscart, Webb, & Beisel, ). For example, Liu and Steiner () found that increasing salinity reduced the ability of a species of zooplankton ( Daphnia pulex ) to develop phenotypic anti‐predator responses to predator kairomones.…”
Section: Introductionmentioning
confidence: 99%